2020
DOI: 10.1136/bmjopen-2020-040726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of backward walking training on knee osteoarthritis: protocol of a systematic review and meta-analysis

Abstract: IntroductionBackward walking (BW) is otherwise known as retrowalking. As opposed to forward walking, BW is a countersequential exercise and is a common method of rehabilitation training and disease-assisted treatment. Studies have shown that BW has a helpful effect on improving lower limb proprioception, gait synergy and improving limb balance. Many studies have concluded that BW can improve the symptoms of patients with knee osteoarthritis (KOA) and can be used for rehabilitation and adjunctive treatment of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, Wu et al. [ 45 ] found a lack of evidence in EBM regarding the use of backward walking, also known as retro-walking, despite its potential benefits in symptom improvement, rehabilitation, and adjunctive treatment for KOA.…”
Section: The Development Practical Process and Future Of Ebrmmentioning
confidence: 99%
“…However, Wu et al. [ 45 ] found a lack of evidence in EBM regarding the use of backward walking, also known as retro-walking, despite its potential benefits in symptom improvement, rehabilitation, and adjunctive treatment for KOA.…”
Section: The Development Practical Process and Future Of Ebrmmentioning
confidence: 99%
“…Many recent studies that are now available have found that retro-walking, also known as backward walking, can lessen knee OA patients' symptoms and is one of their kinetic options. Retro-walking, which is counter-sequential to forward walking and has a beneficial effect on limb balance, gait synergy, and lower limb proprioception, is a useful exercise [30]. A two-minute walk test is also used in this study to assess the functional capacity of the patients.…”
Section: Figure 4: Comparison Of Two-minute Walk Test Scores Between ...mentioning
confidence: 99%